New method and electrophysiological characteristics of LA posterior wall isolation in persistent atrial fibrillation. Issue 10 (19th September 2021) - Liang, Zhuo; Liu, Lifeng; Cheng, Liting; Wang, Zefeng; Zhang, Junmeng; Yang, Wenxue; Wang, Yunlong; Wu, Yongquan
Abstract: Background: Left atrial posterior wall isolation (PWI) is commonly used with persistent atrial fibrillation (AF) ablation. However, potentials are often still recorded in the posterior wall after pulmonary vein isolation (PVI), roof linear ablation, and bottom linear ablation in clinical practice. We aimed to explore the methodological approach and electrophysiological characteristics of PWI. Methods: A total of 36 patients who attended our center with long‐standing persistent AF were retrospectively analyzed. After routine PVI and roof and bottom linear ablation, complete PWI was confirmed in sinus rhythm by voltage mapping and high‐output pacing. Otherwise, activation mapping and voltage mapping were used to guide ablation on the line or inside the posterior wall until bidirectional block was achieved. Results: The first‐pass success rate of PWI was 39%. In the remaining 61% of patients with posterior wall electrograms, activation mapping in sinus rhythm showed that the earliest activation point was not on the ablation line but in a relatively dispersed focal area, possibly related to epicardial muscular sleeve insertion. Voltage mapping revealed a focal high‐voltage area in the posterior wall matching the relatively dispersed earliest activation site, in which an average of five points of ablation achieved complete PWI without serious esophageal injury. The middle zone contained 80% of the additional posterior wall ablation points. Conclusions: PWI was performed safely and effectively with an average of five additional ablation points in the posterior wall in 61% of patients under the guidance of voltage mapping.